2017
DOI: 10.1111/pala.12295
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics as a tool for testing functional and ecological hypotheses in fossil taxa

Abstract: Computational fluid dynamics is a method for simulating fluid flows that has been widely used in engineering for decades, and which also has applications for studying function and ecology in fossil taxa. However, despite the possible benefits of this approach, computational fluid dynamics has been used only rarely in palaeontology to date. The theoretical basis underlying the technique is outlined and the main steps involved in carrying out computer simulations of fluid flows are detailed. I also describe prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 39 publications
(56 reference statements)
0
35
0
Order By: Relevance
“…One key aspect of mesh generation is the geometry of each cell. In Schemes 1 and 4 (Table 1), we employ tetrahedral elements as the base mesh, which is shown to be robust in previous studies for CFD studies and is more appropriate for complex geometry than cube/ hex elements (Adkins and Yan, 2006;Rigby and Tabor, 2006;Shiino et al, 2009;Rahman et al, 2015;Dynowski et al 2016;Rahman, 2017). Scheme 2 applied the ANSYS assembly meshing method, which automatically employs a variety of element types and settings to produce a mesh as a single process.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One key aspect of mesh generation is the geometry of each cell. In Schemes 1 and 4 (Table 1), we employ tetrahedral elements as the base mesh, which is shown to be robust in previous studies for CFD studies and is more appropriate for complex geometry than cube/ hex elements (Adkins and Yan, 2006;Rigby and Tabor, 2006;Shiino et al, 2009;Rahman et al, 2015;Dynowski et al 2016;Rahman, 2017). Scheme 2 applied the ANSYS assembly meshing method, which automatically employs a variety of element types and settings to produce a mesh as a single process.…”
Section: Methodsmentioning
confidence: 99%
“…In all cases, the behavior of these flows are generally governed by the Reynolds-Averaged Navier-Stokes model (Flanagan, 2004;Weymouth et al, 2005;Adkins and Yan, 2006;Rigby and Tabor, 2006;Wilson et al, 2006;Shiino et al, 2009;Hannon, 2011;Dynowski et al 2016;Mossige, 2017;Rahman, 2017). The standard form of the Navier-Stokes equation mathematically approximates laminar flow and general patterns, but does not account for the complexities that arise from flow instability, such as the occurrence and behavior of turbulent eddies (Argyropoulos and Markatos, 2015;Rahman, 2017). Eddies can be simulated by supplementing the Navier-Stokes equation with additional computational algorithms, the options for which vary by software (Iaccarino, 2001;Argyropoulos and Markatos, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The taxa selected occupy a wide range of phylogenetic positions and are representative of the main body shapes and sizes of ichthyosaurs, an advance relative to former studies, which focused only on derived forms [6,11]. Using computational fluid dynamics (CFD) [20], a numerical technique for simulating fluid flows, we tested the hypothesis that the derived fish-shaped ichthyosaurs had acquired morphologies that reduced the energy cost of steady swimming.
Figure 1.Digital models of the ichthyosaurs analysed in this study shown in their phylogenetic context.
…”
Section: Introductionmentioning
confidence: 99%
“…This process is very sensitive and dependent on the material properties such as bone density and mineralization. Subsequently, the virtual model of the object is generated and can be subject to different evolutionary studies using 3D geometric morphometrics (GMM) for ecomorphology (Drake, 2011), finite element analysis for biomechanics (Racicot, 2017;Tseng et al, 2017), or computational fluid dynamics to decipher the behavior of extinct animals in fluid environments (e.g., Rahman, 2017). In addition, such models can be printed out using rapid prototyping to have a physical replica of the object under study and therefore improving the anatomical understanding and opening the possibility of using these models for teaching or public engagement.…”
Section: Introductionmentioning
confidence: 99%